Ecological stoichiometry in planktonic communities of inland waters: anthropic influences and spatial gradients - Fonseca, Layla Mayer (2022)
Ecological stoichiometry is the field of study that relates the chemical composition of organisms to the availability of elements in the environment. Most studies in this field deal with Carbon, Nitrogen and Phosphorus due to their great importance in the composition of organisms for metabolic functions and for their important biogeochemical role. Alfred Redifield, in 1930, associated the chemical composition of marine plankton with the availability of nutrients in the ocean, establishing the Redfield constant of 106 C: 16 N: 1 P. Ecological Stoichiometry is an important approach for the understanding of microbial metabolism, as well as functioning of ecosystems, since bacteria are the basis of trophic relationships and are also connected to the availability of organic matter in the environment, as well as to nutrient cycling. The nutritional composition of bacteria is strongly influenced by the growth rate of these organisms, and therefore, phenomena capable of regulating bacterial metabolism are central to the functioning of aquatic ecosystems. Luminosity, temperature and precipitation are environmental factors capable of affecting the metabolism of organisms that present wide variation with latitude (e.g. increase in average temperature with decreasing latitude). Hence, differences in microbial stoichiometry can be expected at different latitudes in response to these environmental variables gradient. This work aims first to address how Ecological Stoichiometry can explain the functioning of natural aquatic ecosystems, focusing on bacterial communities and seston and also how this science can be used to understand the ecological functioning of ecosystems facing anthropic impacts, such as climate change and excessive nutrient input. Then, we investigated how the latitude in which ecosystems are located and their trophic status can influence the chemical composition of seston and bacteria and how each compartment behaves in different environmental situations established by latitude, such as luminosity and temperature and the availability of nutrients such as N and P, which determine the trophic status of the system. For this, the amounts of nutrients (C, N and P) present in the seston and in the bacterial fractions of 55 lakes along the Americas were determined. The seston C: N, C: P and N: P ratio decreased at higher latitudes, which was not observed for bacteria. When analyzed separately by trophic status, the bacterial and seston C: N decreased with the latitude in eutrophic environments, but not in oligotrophic environments. The C:P ratio of both seston and bacteria did not vary with both latitude and trophic status. The seston N: P ratio in oligotrophic environments decreased with latitude, and the opposite occurs in eutrophic environments. This study highlights the interplay between latitude and trophic state in regulating seston and bacterial stoichiometry.